2019
DOI: 10.3329/bpj.v22i1.40072
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Toxicity Evaluation of Traditional Herb: Lagerstroemia speciosa L. (Banaba) by MCF-7 Cell Line and Brine Shrimp Lethality Bioassay

Abstract: The main objective of this study was to determine the cytotoxicity of crude extract of the leaves of Lagerstroemia speciosa (Banaba). In vitro MCF-7 cell line and in vivo brine shrimp lethality bioassay methods were followed to investigate the cytotoxicity of the selected sample. In this study, the qualitative phytochemical assessment demonstrated the presence of alkaloids, carbohydrate, glycosides, saponins, terpenes, steroids, phenols and flavonoids in Banaba extract. Moreover, the present findings revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The cytotoxic effects of LLE against A549 lung cancer cells caused significant decrease in cell viability in a concentration-dependent manner. Leaves of the L. speciosa plant are rich in polyphenolic compounds [12,45]. Anantharaju et al [46] reported the cytotoxic effects of phenolic compounds against various cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effects of LLE against A549 lung cancer cells caused significant decrease in cell viability in a concentration-dependent manner. Leaves of the L. speciosa plant are rich in polyphenolic compounds [12,45]. Anantharaju et al [46] reported the cytotoxic effects of phenolic compounds against various cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolites quantified in this analysis have a great deal of biological effects and pharmacological properties 49 . These prelims phytochemicals have been observed from the different parts (fruits, leaves and roots) of L. speciosa [53][54][55] . Therefore, the carbohydrates, phenols, proteins, saponins and tannins present in Ee-Ls are the most effective biomolecule in synthesis of Ls-Ag NPs 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…These phyto-compounds are established independently as cytotoxic agents against a variety of cancer cell lines including HepG2 cells. 14,[28][29][30] Recently, studies have explored the cytotoxic potentials of ethanolic and methanolic banaba leaves extract against breast cancer cell lines. 31,32 Therefore, it is suggested that regardless of the cell line, EBLE induced cytotoxicity in HepG2 cells, and this could be due to the presence of above phytoconstituents.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed the presence of active phytocompounds like berberine, and gallic acid in EBLE. These phyto‐compounds are established independently as cytotoxic agents against a variety of cancer cell lines including HepG2 cells 14,28‐30 . Recently, studies have explored the cytotoxic potentials of ethanolic and methanolic banaba leaves extract against breast cancer cell lines 31,32 .…”
Section: Discussionmentioning
confidence: 99%